GASP XVIII: star formation quenching due to AGN feedback in the central region of a jellyfish galaxy. Issue 3 (24th May 2019) - George, K; Poggianti, B M; Bellhouse, C; Radovich, M; Fritz, J; Paladino, R; Bettoni, D; Jaffé, Y; Moretti, A; Gullieuszik, M; Vulcani, B; Fasano, G; et al.
ABSTRACT: We report evidence for star formation quenching in the central 8.6 kpc region of the jellyfish galaxy JO201 that hosts an active galactic nucleus (AGN), while undergoing strong ram-pressure stripping. The ultraviolet imaging data of the galaxy disc reveal a region with reduced flux around the centre of the galaxy and a horse-shoe-shaped region with enhanced flux in the outer disc. The characterization of the ionization regions based on emission line diagnostic diagrams shows that the region of reduced flux seen in the ultraviolet is within the AGN-dominated area. The CO J2−1 map of the galaxy disc reveals a cavity in the central region. The image of the galaxy disc at redder wavelengths (9050–9250 Å) reveals the presence of a stellar bar. The star formation rate map of the galaxy disc shows that the star formation suppression in the cavity occurred in the last few 10 8 yr. We present several lines of evidence supporting the scenario that suppression of star formation in the central region of the disc is most likely due to the feedback from the AGN. The observations reported here make JO201 a unique case of AGN feedback and environmental effects suppressing star formation in a spiral galaxy.